Effect of Solutol HS 15 and Cremophor RH 40 on Dissolution and Bioavailability of Nateglinide through Solid Dispersions - Swain, Ranjit Prasad; Subudhi, Bharat Bhusan (Indian Journal of Pharmaceutical Education and Research, 2022)
Introduction: To improve the aqueous solubility and bioavailability of nateglinide, we have earlier used poloxamer 188 and 407. Since solutol HS 15 and cremophor RH 40 are compatible and scalable polymers for industrial applications. Materials and Methods: We developed solid dispersions using these polymers. All data including Fourier transform infrared spectroscopy, differential scanning calorimetry, thermogravimetry analysis, x-ray diffraction and scanning electron microscopy suggested loss of crystallinity and amorphization. The stability of these was demonstrated as per the International Council for Harmonisation norms. Results and Discussion: Cremophor RH 40 (melting method) and solutol HS 15 based (solvent evaporation method) solid dispersions showed the highest saturation solubility (~ 65 fold). The significant difference (p < 0.05) in dissolution efficiency, time taken to release 50 % of drug, mean dissolution time and similarity factor signifies the remarkable enhancement of dissolution in these solid dispersions. Following oral administration of solid dispersions to rabbits, an increase of ~ 2.4 and ~ 1.8 folds in peak plasma concentration, area under curve respectively and decrease in time to reach peak plasma concentration (1 hr) of nateglinide, suggested the effectiveness of solid dispersions to improve the bioavailability. A 170% and 179% increase in relative bioavailability was demonstrated compared to the marketed formulation (Natiz 60) for these solid dispersions. Conclusion: Cremophor RH 40 solid dispersion showed relatively late release but a higher In vitro-in vivo correlation. It may be suggested that cremophor RH 40 promotes better absorption as compared to solutol HS 15 based solid dispersion.
Keywords: Amorphization; Bioavailability enhancement; In vitro-in vivo correlation; Solutol HS 15; Cremophor RH 40; Pharmacokinetic